Snoring Sound Characteristics are Associated with Common Carotid Artery Profiles in Patients with Obstructive Sleep Apnea [Corrigendum] - Chuang HH (Dove Medical Press, 2021)
Chuang HH, Liu CH, Wang CY, et al. Nat Sci Sleep. 2021;13:1243–1255. Page 1253, Acknowledgment section, second line, the text “CMRPG3F1091-3” should read “CMRPG3G1381-3”. The authors apologize for this error. Read the original article